تحليل الأفعال الكلامية الإلوكوسية في حوار الرسوم المتحركة الفربي - Nurfajrin Hasan, Sri; Susilo, Joko (Journal of Arabic Language and Literature (ALLAIS), 2022)
This research has two objectives. The first objective is to describe the form of illocutionary speech acts in the dialogue of the cartoon film "al-Farabi" by Abu Giyas. The second objective is to find out the function of illocutionary speech acts in the dialogue of the cartoon film "al-Farabi" by Abu Giyas. This research is a qualitative research with descriptive analysis method. The data source of this research is the dialogue of the film "al-Farabi" by Abu Giyas. The research data are oral data containing illocutionary speech acts which include the form of illocutionary speech acts and the function of illocutionary speech acts in the dialogue film "al-Farabi" by Abu Giyas. The data collection technique used the listening method with the free-of-conversation listening technique followed by a transcript, and the last one was the note-taking technique. The validity of the data is done by using the persistence of observation of triangulation theory. The conclusion from the results of this study is related to illocutionary speech acts seen from the aspect of form and function. In the dialogue of the film "al-Farabi" found five forms of illocutionary speech acts, namely Assertive, Directive, Expressive, Commissive and Declaration. Judging from the function of illocutionary speech acts, the dialogue of the film "al-Farabi" has various functions. Assertive illocutionary speech acts have the functions of stating, suggesting, claiming, affirming, and complaining. The form of directive illocutionary speech acts has the functions of ordering, commanding, pleading, and recommending. Expressive illocutionary speech acts have the functions of praising, expressing sadness, thanking, and apologizing. The form of commissive illocutionary speech acts has the function of promising and offering something. The illocutionary speech act form of declaration has the function of surrender.